2015
DOI: 10.1088/1367-2630/17/3/033041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of conditional state-engineering quantum processes by coherent state quantum process tomography

Abstract: Conditional quantum optical processes enable a wide range of technologies from generation of highly non-classical states to implementation of quantum logic operations. The process fidelity that can be achieved in a realistic implementation depends on a number of system parameters. Here we experimentally examine Fock state filtration, a canonical example of a broad class of conditional quantum operations acting on a single optical field mode. This operation is based upon interference of the mode to be manipulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In fact, the detection can not discriminate perfectly between different photon-number states, resulting in an incoherent mixture of distinct contributions. This is similar to the heralding effects on conditional operations found recently in Fock-state filtration 50 . The sheer effect is a reduction of the maximal photon number at which a satisfactory fidelity can be found with respect the results reported in Fig.…”
Section: Resultssupporting
confidence: 89%
“…In fact, the detection can not discriminate perfectly between different photon-number states, resulting in an incoherent mixture of distinct contributions. This is similar to the heralding effects on conditional operations found recently in Fock-state filtration 50 . The sheer effect is a reduction of the maximal photon number at which a satisfactory fidelity can be found with respect the results reported in Fig.…”
Section: Resultssupporting
confidence: 89%
“…The studies on FSF imperfection involve multiple variables, such as the input photon distributions, the single photon generation rate, the FSF sensitivity k (used to filter out |k〉), and the photon detection sensitivity, where its efficiency cannot be simply characterized. In 2015, an experimental model of an imperfect FSF was proposed and studied from three aspects 32 : the use of photon detectors that cannot distinguish events between one photon detection and higher-photon-number detection, the imperfect single photon catalyst that is actually a superposition of a single photon state and a vacuum state, and mode mismatch between the input state and the single photon catalyst; and they calculated the success probability of an imperfect FSF that can filter out |1〉 from a coherent state using Eq. (14) in that paper 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, an experimental model of an imperfect FSF was proposed and studied from three aspects 32 : the use of photon detectors that cannot distinguish events between one photon detection and higher-photon-number detection, the imperfect single photon catalyst that is actually a superposition of a single photon state and a vacuum state, and mode mismatch between the input state and the single photon catalyst; and they calculated the success probability of an imperfect FSF that can filter out |1〉 from a coherent state using Eq. (14) in that paper 32 . This structure can be utilized to study the FSF efficiency p FSF (k) with other photon number sensitivity k, which is one of the next research directions based on the theoretical work here.…”
Section: Discussionmentioning
confidence: 99%
“…continuous variable) systems, according to the formulation by Anis and Lvovsky [40]. Cooper et al reported that the algorithm ran for 6.5 hours (with a machine precision stopping rule) to reconstruct a d = 6 conditional state engineering process [41]. Fedorov et al performed QPT of a beamsplitter, revealing the Hong-Ou-Mandel effect [42].…”
Section: A Benchmark 1 : Diluted Iterationsmentioning
confidence: 99%